Pasolini Overseas: His Reception in Canada - Ferraro, Alessandra (Italian Canadiana, 2024)
After briefly tracing the history of Pier Paolo Pasolini’s travels in the Americas through the photographs that immortalize him, I focus my attention on the reception of his work and thought in Canada. I consider it significant especially in the context of gay, queer, and LGBTQ+ culture and among Italian-Canadian intellectuals. In the Canadian context, characterized by linguistic and cultural plurality, writers and essayists of Italian descent translate Pasolini’s works, absorb his lessons, and draw on his thought to explore mainly identity-related issues. In the queer artistic milieu, it will be Pasolini’s biographical journey in particular that attracts the attention of intellectuals and performers who, by manipulating his works and images, transform him into an icon of the different.